Clinical Mycobacterium tuberculosis isolates exhibit a molecular clock rate below 1 SNP per genome per year - Wang, Jun-Li; Chen, Ya-Li; Guan, Cui-Ping; Yu, Kan; Wang, Mao-Shui (Frontiers in Microbiology, 2025)
PurposeTuberculosis (TB) remains a significant global health concern, necessitating effective measures to control the epidemic. Understanding the evolution of Mycobacterium tuberculosis (M. tb) through molecular clock analysis is crucial for tracing outbreaks, managing transmission, and ultimately improving TB management in practice.ResultsA total of 27 studies were included for analysis. The pooled mutation rate was estimated at 0.63 single nucleotide polymorphisms (SNPs) per genome per year [95% confidence interval (CI): 0.51–0.75; 95% predictive interval (PI): 0.04–1.22], significant heterogeneity (I2 = 92.7%, p < 0.001) was observed. Clinical strains had a mutation rate of 0.55 SNPs per year (95% CI: 0.45–0.65; 95% PI: 0.12–0.98), while model strains showed a higher rate of 1.14 SNPs per year (95% CI: 0.68–1.60; 95% PI: −0.22-2.50; Meta-regression analysis, p = 0.006). Mutation rates did not significantly differ between transmission events and reactivation or single episodes (p = 0.497).ConclusionThe mutation rate of clinical M. tb strains is below 1 SNP per genome per year, indicating evolutionary stability in clinical settings. This finding is important for TB outbreak reconstructions and public health strategies. Future research should refine subgroup analyses based on infection characteristics for more precise molecular clock estimates.Systematic review registrationPROSPERO, identifier CRD42024595161.